Engaging children in mathematical discourse: a kindergarten teacher’s multimodal participation - Breive, Svanhild (NOMAD Nordic Studies in Mathematics Education, 2019)
This article reports from a case study which investigates a kindergarten teacher’s multimodal participation in a teaching-learning activity involving addition and counting. By multimodal participation the kindergarten teacher engages nine children (age 4.9–5.9) in mathematical discourse and supports their opportunities for learning. Implications for practice are that kindergarten teachers (and school teachers) can benefit from being consciously aware of the affects their bodily actions have on children’s mathematical reasoning and how they can engage children in mathematical discourse without having to ”teach” (i.e., tell) children mathematical concepts and relations. The article also considers how kindergarten teachers can prepare for a smooth transition to school by introducing children to mathematics through semi-structured activities.